Two Weighted $BMO$ Estimates for the Maximal Bochner-Riesz Commutator (Analysis in Theory and Applications, 2013)
In this note, the author prove that maximal Bochner-Riesz commutator $B^b_{δ,*}$ generated by operator $B_{δ,*}$ and function $b\in BMO(ω)$ is a bounded operator from $L^{p}(μ)$ into $L^{p}( u)$, where $ω\in(μ u^{-1})^{\frac{1}{p}},μ, u\in A_p$ for $1 < p